2019
DOI: 10.1111/gbb.12543
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated pseudogenization of trace amine‐associated receptor genes in primates

Abstract: Trace amines (TAs) in the mammalian brain have been investigated for four decades. Trace amine‐associated receptors (TAARs) were discovered during the search for receptors activated by TAs. TAARs are considered a second class of vertebrate olfactory receptors and successfully proliferated in conjunction with adaptation to living on the ground to detect carnivore odors. Thus, therian mammals have a high number of TAAR genes due to rapid species‐specific gene duplications. In primate lineages, however, their gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 79 publications
(193 reference statements)
0
6
0
Order By: Relevance
“…An evolutionary genetic survey demonstrated that TAAR5 is the most conserved TAAR subtype among all characterized mammalian species investigated so far [13]. Intriguingly, this receptor became the pseudogene in some primates [14] and its affinity for ligands varies in different species. For example, di-and trimethylamine display no agonistic activity for TAAR5 in most primates and cattle, but activate TAAR5 in mouse, rat, and dog [15].…”
Section: Introductionmentioning
confidence: 99%
“…An evolutionary genetic survey demonstrated that TAAR5 is the most conserved TAAR subtype among all characterized mammalian species investigated so far [13]. Intriguingly, this receptor became the pseudogene in some primates [14] and its affinity for ligands varies in different species. For example, di-and trimethylamine display no agonistic activity for TAAR5 in most primates and cattle, but activate TAAR5 in mouse, rat, and dog [15].…”
Section: Introductionmentioning
confidence: 99%
“…The fate of a gene duplicate includes several potential paths ( Hahn 2009 ; Teufel et al 2016 ; Yohe et al 2019b ). First, the duplicated gene may be completely redundant and not be expressed, and thus it could accumulate a deleterious mutation that may render it a pseudogene ( Eyun 2019 ). Second, one of the two copies may be released from purifying selection and accumulate new mutations that enable new function ( Pegueroles et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fate of a gene duplicate includes one of several paths (Hahn 2009; Teufel et al 2016; Yohe et al 2019b). First, the duplicated gene may be completely redundant and not be expressed, and thus accumulate deleterious mutation that may render it a pseudogene (Eyun 2019). Second, one of the two copies may be released from purifying selection and accumulate new mutations that enable new function (Pegueroles et al 2013).…”
Section: Introductionmentioning
confidence: 99%